Assessment of water, sanitation and hygiene services within nineteen Rohingya camps in Cox’s Bazar, Bangladesh in 2022 - Saira Butt; Md. Samiur Rahman Chowdhury; Sohana Sadique; Abdullah Al Faisal; Adrien Mahama; Alexander Gorski; Biserka Pop-Stefanija; David Beversluis; Jackson Mojong Lochokon; Kalyan Velivela; Kennedy Uadiale; Md. Mahbubur Rahman; et al. (BMC Health Services Research)
Abstract Background Since August 2017, approximately 960,000 Rohingya refugees have settled in Cox’s Bazar, Bangladesh. Water, sanitation, and hygiene (WASH) infrastructure and programs were implemented across the camps to address the needs of the population and reduce the burden of linked infectious diseases. However, monitoring and maintenance of this infrastructure has been inconsistent. This study aimed to assess progress in WASH in the camps of Cox’s Bazar since the early emergency phase in 2018, and to update the priorities for intervention. Methods From January to March 2022, a lot quality assurance sampling (LQAS) survey was conducted across 19 camps. Nineteen households were randomly selected per camp. Data on access to and quality of WASH services, household practices, and health outcomes including skin infections among children under five years of age were collected. Crude and weighted averages with 95% confidence intervals were calculated for each indicator and compared with targets pre-defined based on Sphere guidelines and Médecins Sans Frontières WASH experts. Chi-squared tests were used to compare the results to a 2018 LQAS survey. Results More than half of the indicators (59%; 16/27) did not meet the pre-determined targets. Performance was adequate on three of five water quality and supply indicators, with less than half of households (44%, 95% CI: 39–49%) reporting that water was continuously available in the past week. Regarding water storage, performance on three indicators was considered adequate, as the proportion of households that keep water for less than one day was 27% (95% CI: 23-32%). Of six hygiene indicators, adequate performance was identified for only one. Performance on the sanitation indicators was inadequate, with 11% (95% CI: 8-15%) of households using an improved sanitation facility. In solid waste management, two of four indicators suggested adequate performance, and for health outcomes, the proportion of children who hadn’t shown any skin infection was inadequate at 69% (95% CI: 64-73%). Conclusions Improvements in the WASH situation in Cox’s Bazar have been observed in 2022 compared to 2018. However, significant gaps remain in water supply, sanitation facilities, and hygiene services. LQAS can be an effective monitoring tool to support long-term multisectoral interventions in protracted emergencies.